(untitled) (Bangladesh Journal of Pharmacology, 2015)
Common chemotherapeutic agents such as oxaliplatin often cause neuropathic pain during cancer treatment in patients. Such neuropathic pain is difficult to treat and responds poorly to common analgesics, which represents a challenging clinical issue. Fisetin is a naturally occurring flavonoid and this study tested the potential anti-hyperalgesic effects of fisetin in a mice model of oxaliplatin-induced neuropathic pain. Fisetin (1-4 mg/kg, i.p.) did not significantly alter the mechanical hypersensitivity in oxaliplatin-treated mice but produced a dose-dependent anti-hyperalgesic effect during repeated treatment. Repeated treatment with fisetin also prevented chronic neuropathic pain-induced depressive-like behavior in a forced swimming test. Both the antihyperalgesic and the antidepressant-like effects of fisetin can be blocked by a selective 5-HT1A receptor antagonist WAY100635 (1 mg/kg). Together, these results demonstrate that fisetin has significant analgesic efficacy against chronic neuropathic pain, which could be a useful analgesic in the management of neuropathic pain.